Dual antiplatelet therapy duration after percutaneous coronary intervention in patients with indication to oral anticoagulant therapy. A systematic review and meta-analysis of randomized controlled trials. Issue 3 (25th November 2022) - Montalto, Claudio; Costa, Francesco; Leonardi, Sergio; Micari, Antonio; Oreglia, Jacopo A; Vranckx, Pascal; Capodanno, Davide; ten Berg, Jurriën; Lopes, Renato D; Valgimigli, Marco
Abstract: Aims: Optimal duration of dual antiplatelet therapy (DAPT) in patients with concomitant indication to oral anticoagulation (OAC) is still debated. Methods and results: A systematic review was performed on electronic databases to search for randomized controlled trials comparing an abbreviated or prolonged (≥3 months) DAPT regimen in patients with OAC and they were analysed in the framework of standard and network meta-analyses. Co-primary endpoints were major or clinically relevant non-major bleedings (MCRB) and major bleeding, while the composite of major adverse cardiovascular events (MACE) was the key safety endpoint. Five studies and 7 665 patients (abbreviated DAPT n  = 3 843; prolonged DAPT n  = 3 822) were included. Both MCRB and major bleeding were lower with abbreviated DAPT [risk ratio (RR) 0.69 (0.52–0.91); P  = 0.01 and 0.70 (0.52–0.95); P  = 0.01, respectively] while MACE [RR: 0.96 (0.70–1.33); P  = 0.6], all-cause death, cardiovascular death, stent thrombosis, or myocardial infarction did not differ. Network meta-analysis showed that peri-procedural DAPT had the highest probability to prevent MCRB and major bleeding (97.1 and 92.0% respectively) when compared with both short (4–6 weeks) and longer (≥3 months) DAPT regimens. Sensitivity analyses and meta-regressions showed consistency in different clinical scenarios and suggested a larger bleeding reduction with P2Y12 inhibitors vs. aspirin after DAPT discontinuation. Conclusion: In patients undergoing PCI with concomitant OAC indication, an abbreviated DAPT regimen reduced MCRB and major bleeding without increasing MACE or other ischaemic events. Peri-procedural DAPT and P2Y12 inhibitor monotherapy after DAPT withdrawal appear to be the best strategies to optimize the bleeding and ischaemic risk tradeoff. Trial registration. PROSPERO CRD284001 Graphical Abstract: